Peningkatan Efisiensi Biaya Melalui Activity Based Management - Fatimah Annisa; Agus Arief Santoso (Jurusan Akuntansi Politeknik Negeri Malang, 2020)
This research aims to analize cost efficiency enhancement through implementation of Activity Based Management. The data of this research are collected by observation, interview and documentation. As the first step of this analysis production cost was calculated with Activity Based Costing method, then researchers reduce nonvalue added activity with Activity Based Management. This research showed a difference between traditional method (that company is currently executing) and Activity Based Costing method. The results are products SKT, SPM and TIS are valued undercost, while SKM is valued overcost. Activity Based Management implementation has increased efficiency of factory overhead cost without reducing the product quality. Abstrak Penelitian ini mengalisis peningkatan efisiensi biaya produksi melalui implementasi Activity Based Management. Data yang digunakan diperoleh dengan observasi, wawancara, dan dokumentasi. Langkah pertama pada penelitian ini adalah menghitung biaya produksi menggunakan Activity Based Costing, selanjutnya mengurangi aktivitas tidak bernilai tambah dengan Activity Based Management. Hasilnya menunjukkan selisih biaya antara metode tradisional yang diterapkan perusahaan dengan Activity Based Management. Selanjutnya untuk produk SKT, SPM, dan TIS mengalami undercosting, sedangkan SKM mengalami overcosting. Activity Based Management telah meningkatkan efisiensi biaya overhead pabrik tanpa menurunkan kualitas produk.